2004
DOI: 10.1021/ma0488156
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Miscibility on the Ionic Conductivity of LiClO4/PEO/PCL Ternary Blends

Abstract: We demonstrate that miscibility affects the ionic conductivity of ternary polymer blends of lithium perchlorate (LiClO4), poly(ethylene oxide) (PEO), and poly( -caprolactone) (PCL). Although individually these three binary blends are fully miscible, a closed immiscibility loop exists in the ternary blend phase diagram as a result of the complicated interactions among LiClO4, PEO, and PCL. The addition of PCL suppresses the crystallization of PEO and results in higher ionic conductivity. FTIR spectroscopy studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 19 publications
(36 reference statements)
1
52
1
4
Order By: Relevance
“…In a related phenomenon, the alloy Cu-Au-Ni mixture shows a closed loop miscibility gap of their solid solutions (25)(26)(27). Similar phase behavior has been found in a polymer blend for which there is spectroscopic evidence for a pairwise binding of two components (28).…”
Section: Discussionsupporting
confidence: 57%
“…In a related phenomenon, the alloy Cu-Au-Ni mixture shows a closed loop miscibility gap of their solid solutions (25)(26)(27). Similar phase behavior has been found in a polymer blend for which there is spectroscopic evidence for a pairwise binding of two components (28).…”
Section: Discussionsupporting
confidence: 57%
“…Polymer electrolytes which are complexes of solvent-free polar polymers and inorganic metal salts are prepared by dissolving salts in high-molecular-weight polymer hosts. Polymer electrolytes have been studied extensively by researchers because of their potential applications, namely, in high-energy density batteries and fuel cells [2]. The key advantages of solid polymeric electrolytes over liquid electrolytes are good mechanical properties, ease of fabrication to thin films, desirable sizes, and their capability to form proper electrode-electrolyte contact [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polymers have attracted much attention in biomedical application [9]. Previous studies [2] have shown that PCL can be used as a polymer matrix for the preparation of polymer electrolytes due to the existence of carbonyl functional groups in its backbone structure. Thus, the ability of PCL as a host polymer is due to the presence of carbonyl groups in its structure that can dissolve inorganic salt as a result of electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic conductivities increased with the increase of salt concentration up to 5 wt.%, after which they gradually decreased with increasing salt concentration. The increase of ionic conductivity in polymer electrolytes is attributable to the increased number of charge carriers, but the decrease at higher salt concentrations is considered to be because of the formation of ion pairs in the polymer electrolytes [23][24][25]. As a result, the maximum ionic conductivity at room temperature was achieved as 3.7×10 −5 S/cm at 5 wt.% of salt concentration.…”
Section: Characterization Of Polymer Electrolytesmentioning
confidence: 99%